Swot Analysis as a Business Strategy to Increase Competitiveness at Rupat Island Depot PT. Pantja Surya - Tya Wildana Hapsari Lubis (Enrichment : Journal of Management, 2021)
The purpose of this research is to formulate and determine the most appropriate business strategy to increase competitiveness at the Rupat Island Depot, PT. Pantja Surya to remain able to compete and excel among competitors. This type of research is descriptive qualitative and the nature of this research is exploratory. The informants in this study were stakeholders. Methods of data collection is done by observation, study documentation, and in-depth interviews. The method of data analysis was carried out by analyzing IFE and EFE matrices, SPACE matrices, and SWOT matrices. This study resulted in 1) 15 points of internal factors consisting of 8 strength factors and 7 weakness factors. 2) 12 points for external factors consisting of 6 opportunity factors and 6 threat factors. This research resulted in a growth and build strategy, this is shown from the results of the internal-external matrix is in the cell division I, while the SPACE matrix results in a business competition position that is in the II quadrant, namely an aggressive strategy, then in the SWOT matrix the results of this study are to utilize the SO (strength- opportunities) strategy.